Стихияның 4-ші үйлесімі–адам денсаулығына ашылған жол - Дикаревич, Л.М.; Имангаликова, И.Б.; Базарбаева, Б.Е. (My University, 2013)
Unconventional methods of recovery are confident in the training workshops complement the traditional methods, increasing student interest in physical training and helping to strengthen their health. This article discusses some aspects of health technology "Balance of 4 elements."